2021
DOI: 10.1007/s00018-021-03944-1
|View full text |Cite|
|
Sign up to set email alerts
|

The molecular identity of the TLQP-21 peptide receptor

Abstract: The TLQP-21 neuropeptide has been implicated in functions as diverse as lipolysis, neurodegeneration and metabolism, thus suggesting an important role in several human diseases. Three binding targets have been proposed for TLQP-21: C3aR1, gC1qR and HSPA8. The aim of this review is to critically evaluate the molecular identity of the TLQP-21 receptor and the proposed multi-receptor mechanism of action. Several studies confirm a critical role for C3aR1 in TLQP-21 biological activity and a largely conserved mode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 79 publications
(237 reference statements)
1
12
0
Order By: Relevance
“…TLQP-21 is a neuropeptide with important endocrine and enteroendocrine functions demonstrated by multiple groups ( 2 , 3 ). Several studies have reported the complement receptor C3aR as an endogenous receptor for TLQP-21 ( 3 , 7 , 8 , 13 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…TLQP-21 is a neuropeptide with important endocrine and enteroendocrine functions demonstrated by multiple groups ( 2 , 3 ). Several studies have reported the complement receptor C3aR as an endogenous receptor for TLQP-21 ( 3 , 7 , 8 , 13 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, TLQP-21 is a 21-residue peptide derived from the C-terminus (residues 556-576) of the VGF precursor protein (3). Using the expression of VGF mRNA as a proxy, past studies have suggested the expression of TLQP-21 in the central and peripheral nervous system and in several neuroendocrine glands including the pancreas, adrenal medullar and pituitary, however, further investigation using more specific molecular tools are needed to confirm these findings (2)(3)(4). TLQP-21 possesses pleiotropic roles in physiology and cell biology, including reducing obesity by decreasing food intake and/or increasing energy expenditure; potentiating adrenergic-induced lipolysis in adipocytes; modulating gastric contractility and acid secretion; reproduction; nociception; neuroprotection and modulation of microglia functions (2,3).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations